Micro-credentials as an alternative means of recognising qualifications in education - A. A. Muravyeva; O. N. Oleynikova (Russian State Vocational Pedagogical University, 2024)
Introduction. The research relevance is conditioned by the necessity for a systematic analysis of the phenomenon of alternative evidence, including micro-credentials, within the context of the emerging discourse in Russia. Various needs and expectations of stakeholders lead to increasing contradictions in the recognition of qualifications, career paths, and educational process goals. In particular, there is a growing demand from students for relevant, concise, and practical programmes. Educational organisations require an effective tool for building confidence and accrediting programmes. Employers need to understand the content of competencies, while the public sector aims to reduce training duration, enhance employability, and improve the return on investment in education. The increasing competition in the education system, within the context of new alternative qualification mechanisms, presents challenges for formal education. However, it also brings forth a number of new opportunities by strengthening the close links between stakeholders. The concept of micro-credentials is closely tied to the increasing entrepreneurial nature of educational organisations in vocational education. This connection is evident in their integration into national and regional development agendas, their promotion of innovative dynamics, and their contribution to economic growth. Consequently, educational organisations in vocational education play a crucial role as agents of social transformation.Aim. The present research aimed to conduct a scoping study on the concept of micro-credentials as an alternative model for recognising and validating competencies beyond traditional qualifications in order to define their role as a means of interaction between different actors, to identify trends, opportunities, and challenges associated with their implementation, and formulate general design principles, key factors, and the value of a micro-credentials system to meet the needs of all stakeholders.Methodology and research methods. The study is methodologically grounded in conceptual research within the framework of actor-network theory of socio-pedagogical interaction. It also involves a diachronic examination of the formation of various aspects of micro-credentials in subsystems and a system-structural analysis of the development of the genesis of micro-credentials. The study employed various research methods, including analysis, generalisation, case study, and comparative analysis, to identify trends in the development of alternative methods for recognising qualifications. Additionally, a conceptual and terminological method was used to define the conceptual content of micro-credentials. The study also utilized methods such as analogy, abstraction, social design, and multifactor interpretation to analyse the functioning of the micro-credentials ecosystem.Results. The authors emphasized general principles of micro-credentials design, proposed strategies for implementation, outlined potential benefits of integrating them into practice for various target groups, states, and societies, and discussed associated risks and challenges. It is suggested and substantiated that the maximum socially useful implementation of the micro-credentials concept is possible if it is recognised as a socio-pedagogical innovation implemented within the framework of an ecosystem embedded in the innovation spiral formed by complex interactions among different actors, including government, enterprises, and educational organizations.Scientific novelty. For the first time, this study presents the interpretation of micro-credentials in the context of adaptation to Russian realities. It also introduces new approaches to the potential use of micro-credentials as an alternative to formal education for recognising and validating qualifications within the mechanism of individual competency accumulation and expansion. Furthermore, it highlights the collective outcome of the formation of an interactive system involving key actors such as education, the public sector, and the private sector.Practical significance. The results of the study can be utilized to advance both theoretical discourse in the study area and to develop specific measures for implementing micro-credentials.